18F‐FDG‐PET/CT predicts early tumor recurrence in living donor liver transplantation for hepatocellular carcinoma. (25th October 2012) - Lee, Seung Duk; Kim, Seong Hoon; Kim, Young‐Kyu; Kim, Chulhan; Kim, Seok‐Ki; Han, Sung‐Sik; Park, Sang‐Jae
Summary The prognosis including 18F‐fluorodeoxyglucose positron emission tomography/computed tomography (18F‐FDG‐PET/CT) for the early recurrence for hepatocellular carcinoma (HCC) after living donor liver transplantation (LDLT) was not well established. Consecutive patients who underwent 18F‐FDG‐PET/CT and subsequent LDLT for HCC from March 2005 to June 2011 were enrolled. The 191 patients with a median follow‐up of 26.1 months were evaluated. There were 20 patients (10.5%) with early recurrence (≤6 months), 18 patients (9.4%) with late recurrence (>6 months), and 153 patients (80.1%) with no recurrence. Fifty‐five patients (28.8%) displayed increased PET/CT tumor uptake. Three‐year overall and disease‐free survival for PET/CT‐positive patients were 65.5% and 57.1%, respectively, while PET/CT‐negative patients showed respective values of 89.8% and 86.8% (P = 0.001 vs. P < 0.001). Tumor variables associated with PET/CT‐positive finding were preoperative AFP level, Milan, UCSF criteria, maximum tumor size, total tumor size, differentiation, vascular invasion, and serosal invasion. PET/CT‐positive status was identified as an independent prognostic factor for disease‐free survival influencing early recurrence in multivariable analysis (HR 3.945, 95% CI 1.196–13.016, P = 0.024). 18F‐FDG‐PET/CT is an independent and significant predictor of early tumor recurrence in LDLT for HCC.